An innovative technique of hydrosurgery in the treatment of osmidrosis. (3rd April 2021) - Wu, Minliang; Dai, Haiying; Zhu, Ji; Xu, Jianguo; Lv, Chuan; Sun, Mengyan; Xue, Chunyu; Wang, Yuchong
Abstract: Background: We aimed at evaluating the effects of hydrosurgery and traditional surgical approach with two parallel incisions in the treatment of osmidrosis. Methods: This prospective study enrolled patients with axillary osmidrosis between January 2015 and November 2016. For hydrosurgery, a 1-cm-long incision was made in the middle of the posterior long axis. The hand piece was turned upside down and processed in a 'W-O' way. For traditional method, two 3-cm-long parallel incisions were made transversely. Patient demographics, complications, duration of procedures and the outcomes were collected and compared. All patients had a follow-up period of 24–36 months. Results: A total of 93 patients were included: 41 patients in hydrosurgery group and 52 patients in traditional method group. No severe complications occurred in the hydrosurgery group, while necrosis occurred in six sides of axillae of traditional surgical group. No recurrence occurred in both groups. Both groups showed similar odor and hair growth reduction rate. Only one in 82 sides occurred slight scar formation, while in traditional group, 22 sides of axillae formed scars ( p < .001). Conclusions: The application of hydrosurgery in the treatment of osmidrosis is efficient and effective. Moreover, it has less postoperative complications, and high patient satisfaction rates.